THE RELATIONSHIP BETWEEN PERFORMANCE AND BENEFITS OF AGRICULTURAL COOPERATIVE TOWARD FARMERS’ ECONOMY AND BEHAVIOUR IN THE DISTRICT OF KOLAKA - Ilma Sarimutaqiyma Rianse; Usman Rianse; Slamet Hartono; Any Suryantini; Wa Kuasa (International Journal of Sustainable Tropical Agricultural Sciences (IJSTAS), 2014)
This study aimed to determine: (1) an analysis of the cooperative’s performance based on the agricultural criteria in the district of Kolaka, according to the guidelines on cooperative fostering and cooperative classification; (2) the performance of the cooperative as perceived by farmers and cooperatives management; (3) determine the benefits gained by farmers as members of cooperatives; (4) an analysis of the relationship between performance and the benefits obtained by farmers as a cooperative member. The results showed that, based on the Guidelines for Cooperatives Classification, the performance of agricultural cooperatives in Kolaka in 2007 was on the average of 61.58 and fell within the “quite well” category. In 2008 the average performance of 62.05 and cooperatives are included in the category quite well. In2009, the average performance of the cooperatives was 62.38, remaining in the same category. In 2010 the average performance was 61.28, also staying in the category of “quite well”. Furthermore, the management of cooperatives as well as the majority of stakeholders considered that the agricultural cooperatives in Kolaka met the criteria of “quite well”, as many as 48.75%. The majority of respondents (65%) considered the agricultural cooperatives in Kolaka helpful. Based on SEM analysis, the relationship of the agricultural cooperative performance was found to be positively correlated to the benefits obtained by farmers. Standardized coefficient value of 0.85 has a value of 14.40t statistic. Standardized coefficient value of 0.85 indicates that the performance and benefits of the cooperative have a real relationship closeness. Sequentially the components of performance that contribute from the largest to the smallest are, firstly, the concern for the community, which is equal to0.86. The component of voluntary and open membership component is 0.80. The component of democratic control by members is 0.79. The component of economic participation of member is 0.71. And the component of education and training is 0.25. Regarding the components of the cooperative benefits, the components that contributes sequentially, from the largest to the smallest, are the economic benefits of marketing, that is equal to 0.96;the benefits of a large savings and loan with 0.88; the economic benefits of farmers needs 0.86; and social benefits 0.48.